2015
DOI: 10.1182/blood.v126.23.1272.1272
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-E2 Related Factor 2 (NRF2) on Chemotherapy Resistance in Acute Myeloid Leukemia (AML) and the Effect of Pharmacological Inhibition of NRF2

Abstract: Although 70-80% of Acute Myeloid Leukemia (AML) patients achieve complete remission with the induction therapy consisting of a combination of Cytarabine (Ara-C) and Daunorubicin (Dnr), the overall survival is dismal with disease relapse, drug resistance and toxicities as the major causes of treatment failure. Single agent arsenic trioxide (ATO) used in acute promyelocytic leukemia (APL or AML-M3) is associated with relatively less toxicities which suggest the possibility of extending its use to elderly non M3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Acute myeloid leukemia (AML) is the most communal acute leukemia in adults and pediatrics (John et al, 2018). Nrf2 could be a perfect druggable target in AML, more effective than drugs that act through ROS, signifying the probability of using Nrf2 inhibitors alone or in combination with chemotherapeutic agents to moderate medication resistance in AML (Karathedath et al, 2017). Encountering THP-1 (human monocytic leukemia cell line) with EGC increased HO-1 and GCLM mRNA expression via PKC and Nrf2 (Ogborne et al, 2008).…”
Section: Leukemiamentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is the most communal acute leukemia in adults and pediatrics (John et al, 2018). Nrf2 could be a perfect druggable target in AML, more effective than drugs that act through ROS, signifying the probability of using Nrf2 inhibitors alone or in combination with chemotherapeutic agents to moderate medication resistance in AML (Karathedath et al, 2017). Encountering THP-1 (human monocytic leukemia cell line) with EGC increased HO-1 and GCLM mRNA expression via PKC and Nrf2 (Ogborne et al, 2008).…”
Section: Leukemiamentioning
confidence: 99%
“…According to whether the occurrence of drug resistance is related to gene mutation, it can be divided into gene instability-dependent and independent drug resistance. Previous reports in AML, and other solid tumors have shown that Nrf2 is associated with resistance to chemotherapeutic agents [33][34][35] . The high Nrf2 expression can lead to the gene instabilityindependent drug resistance in AML, and its mechanism is mostly related to the activation of NF-kB 36 .…”
Section: Discussionmentioning
confidence: 90%
“…The expression level of Nrf2 protein was decreased (65.82±2.36) % in the Nrf2-RNAi- 16 LV infected group, with a statistical difference (P=0.0030), when compared with that of the NC-GFP-LV control group and K562/G01 blank group. Whereas, no difference (P=0.8860) between the NC-GFP-LV control group and K562/G01 blank group was observed ( Figure 3C and Figure 3D).…”
Section: Identification Of a Positive Correlation Between Nrf2 Expresmentioning
confidence: 88%
“…Nrf2 can overcome apoptosis and reduce the susceptibility of AML towards chemotherapeutic agents [14,15]. High Nrf2 expression is related with chemoresistance to Ara-C, DNR, and ATO in AML cell lines and primary AML cells, and knockdown of Nrf2 can increase AML cells predisposition to chemotherapy drugs [11,16]. Some studies also explored to reverse the drug-resistance of human myelogenous leukemia cells and MDS by using Nrf2 inhibitors [11,17].…”
Section: Introductionmentioning
confidence: 99%